British Foreign Policy towards the Palestinian Issue Since 2003 - Mustafa Ibrahim Salman Al-Shammari; Dhari Sarhan Hamadi Al-Hamadani (Tikrit Journal For Political Science, 2017)
The topic area of that’s paper dealing with role of Britain in established of Israel, so the paper argued the historical developments of Palestinian question and Role of Britain Government toward peace process since 1992, and then its insight toward plan of Palestinian State. That’s paper also argued the British Policy toward Israeli violations toward Palestinians people, and increased with settlement policy by many procedures like demolition of houses, or lands confiscation, the researcher argued the Britain position toward that’s violations beside the political developments which happens in Britain after Theresa May took over the power in Ten Downing Street.